Designing a sustaining amplifier for a 17.22 MHz electrostatic resonator based reference oscillator - Roy, S.; Ramiah, H.; Reza, A.W. (2014)
MEMS resonator based oscillators, however, are now a technical reality which are extremely cost-effective, very small in size in comparison with quartz crystal based oscillators and can be fabricated in the conventional CMOS process, monolithically. In this work a new sustaining amplifier is designed for a 17.22 MHz MEMS resonator which has an unloaded quality factor of 1000. A total transimpedance open loop gain of 122 dB-Ω has been achieved over the bandwidth of interest to drive this resonator for a sustained oscillation. Total DC power consumption of this sustaining amplifier is 6.3mW from a 1.8v DC source in 0.18μm CMOS process.